2009
DOI: 10.1074/mcp.m800589-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

From Secretome Analysis to Immunology

Abstract: Dendritic cells are known to be activated by a wide range of microbial products, leading to cytokine production and increased levels of membrane markers such as major histocompatibility complex class II molecules. Such activated dendritic cells possess the capacity to activate naïve T cells. In the present study we demonstrated that immature dendritic cells secrete both the YM1 lectin and lipocalin-2. By testing the ligands of these two proteins, chitosan and siderophores, respectively, we also demonstrated th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 43 publications
1
20
1
3
Order By: Relevance
“…We demonstrated that type I IFNs are crucial for the adjuvanticity of chitosan, both in its ability to promote DC activation in vitro and its ability to enhance cell-mediated immunity in vivo. This observation contrasts with a previous report which proposes a role for TLR4 in chitosan-mediated DC activation (Villiers et al, 2009). We and others have demonstrated the inflammasome-activating potential of chitosan (Bueter et al, 2011, 2014; Mori et al, 2012).…”
Section: Discussioncontrasting
confidence: 99%
“…We demonstrated that type I IFNs are crucial for the adjuvanticity of chitosan, both in its ability to promote DC activation in vitro and its ability to enhance cell-mediated immunity in vivo. This observation contrasts with a previous report which proposes a role for TLR4 in chitosan-mediated DC activation (Villiers et al, 2009). We and others have demonstrated the inflammasome-activating potential of chitosan (Bueter et al, 2011, 2014; Mori et al, 2012).…”
Section: Discussioncontrasting
confidence: 99%
“…However, as with MC-derived particles, some synthetic particles are able to persist within the tissue (data not shown), and these may also promote the function of encapsulated cytokines at the site of injection. Furthermore, although chitosan has been suggested to promote some level of innate immune activation 23 , we find here that particles made from this highly purified chitosan do not, alone, have adjuvant activity, and this property emerges only when the particles are used as carriers for immuno-modulatory cytokines.…”
Section: Differential Particle Loading To Polarize Immune Responsesmentioning
confidence: 63%
“…Responses were also compared with mice administered HA emulsified in the standard vaccine adjuvant, alum, as a positive control. As other groups have reported that chitosan is able to induce innate immune activation on a cellular level 23 , and that different formulations of chitosan complexes have adjuvant activity 24,25 , we included a further control where mice were given HA in combination with empty particles, consisting of only the heparin–chitosan core. We then stained single-cell suspensions from the draining LN for the cellular activation marker of germinal centres, GL7, for quantification by flow cytometry.…”
Section: In Vivo Ln Targeting and Particle-induced Remodellingmentioning
confidence: 99%
“…As a natural polysaccharide, COS is the depolymerized product of chitosan, and has good solubility in water and various biological activities, including immune-stimulant [5], anti-inflammatory [6] and antioxidant properties [7]. Numerous studies have shown that chitosan has beneficial effects on relieving the oxidative stress [8].…”
Section: Introductionmentioning
confidence: 99%